REVEALING THE DILEMMA OF MARRIAGE DISPENSATION REGULATIONS IN INDONESIA - Efrinaldi, Efrinaldi; Jayusman, Jayusman; Yenis, M. (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2023)
This article aims to reveal the regulation of marriage dispensation in Indonesia, which is regulated in Law No. 16 of 2019 concerning amendments to Law No.1 of 1974. Article 7 paragraph (2) states that if there is a deviation from the age provision, the parents of the man or woman can apply for marriage dispensation to the Court, for the sake of al-mashlahat. The focus of this research is how Islamic law analyzes the regulation of marriage dispensation in Law Number 16 of 2019. In this study, a normative legal research method is used, which is also called dogmatic legal research. The results show that Law No. 16/2019 brings the spirit of change regarding the regulation of marriage dispensation and the minimum age of marriage. In addition, Supreme Court Regulation No. 5 of 2019 is a special rule as a form of explanation of procedural law relating to marriage dispensation applications. In the perspective of Islamic Law, it brings al-mashlahat, with the regulation of marriage dispensation in certain circumstances. However, the minimum age of marriage in Islamic law is determined by ihtilam, rusyd, menstruation as physical signs and a certain age, which indicates maturity.